Performance study of digital communication systems in TWDP fading - Zhang, Songze (2016)
In a long-distance wireless-channel transmission, the amplitude, frequency and phase of signals would change randomly. In order to analyze and predict received signals, we need to analyze fading channels that signals go through. Basically, it is assumed that the traditional fading models follow Rayleigh distribution, Rician distribution or Nakagami-w distribution. However, we find that in some cases the real fading sometimes is worse than traditional fading. Thus, Durgin has discovered a new analytical fading distribution called two-wave with diffuse power (TWDP) fading to describe this type of small-scale fading. Based on this new fading model, we analyze its performance with different modulation schemes, such as binary phase signal keying (BPSK), differential phase signal keying (DPSK) and binary frequency signal keying (BFSK). Moreover, diversity combining techniques are used to reduce the effects of multipath fading at receivers. The objective of these techniques is to improve the signal-to-noise ratio (SNR) of the received signal, making better system performance. Some of the traditional diversity-combining techniques are maximal-ratio combining (MRC), equal-gain combining (EGC), selection combining (SC), and switched combining. We would discuss the performance with these diversity combining techniques. In general, we investigate essential properties and BER performance of this new fading model.